Permafrost and groundwater interaction: current state and future perspective - Diak, Magdalena; Böttcher, Michael Ernst; Ehlert von Ahn, Cátia Milene; Hong, Wei-Li; Kędra, Monika; Kotwicki, Lech; Koziorowska-Makuch, Katarzyna; Kuliński, Karol; Lepland, Aivo; Makuch, Przemysław; Sen, Arunima; Winogradow, Aleksandra; et al. (Frontiers in Earth Science, 2023)
This study reviews the available and published knowledge of the interactions between permafrost and groundwater. In its content, the paper focuses mainly on groundwater recharge and discharge in the Arctic and the Qinghai-Tibet Plateau. The study revealed that the geochemical composition of groundwater is site-specific and varies significantly within the depth of the aquifers reflecting the water-rock interactions and related geological history. All reviewed studies clearly indicated that the permafrost thaw causes an increase in groundwater discharge on land. Furthermore, progressing climate warming is likely to accelerate permafrost degradation and thus enhance hydrological connectivity due to increased subpermafrost groundwater flow through talik channels and higher suprapermafrost groundwater flow. In the case of submarine groundwater discharge (SGD), permafrost thaw can either reinforce or reduce SGD, depending on how much pressure changes affecting the aquifers will be caused by the loss of permafrost. Finally, this comprehensive assessment allowed also for identifying the lack of long-term and interdisciplinary in situ measurements that could be used in sophisticated computational simulations characterizing the current status and predicting groundwater flow and permafrost dynamics in the future warmer climate.